Attachment of −tBu groups to aza-BODIPY core at 3, 5-sites with ultra-large Stokes shift to enhance photothermal therapy through apoptosis mechanism. (December 2022) - Li, Ran; Ren, Junyi; Zhang, Dongxiang; Lv, Meiheng; Wang, Zhan; Wang, Huan; Zhang, Shan; Du, Jianjun; Jiang, Xin-Dong; Wang, Guiling
Abstract: By the introduction of the − t Bu groups into aza-BODIPY core, di- tert -butyl-substituted aza-BODIPYs at 3, 5-sites (tBuazaBDP s) were prepared for the first time. Based on the X-ray analysis of CN-tBuazaBDP, this molecular structure is twisted. Near-infrared dye SMe-tBuazaBDP has the ultra-large Stokes shift (152 ​nm) in aza-BODIPY system, combining with the twisted intramolecular charge transfer and the free rotation of the −t Bu groups at 3, 5-sites. Although the barrier-free rotors of the distal −t Bu groups in SMe-tBuazaBDP result in low fluorescence quantum yield, the photothermal conversion efficiency is markedly enhanced. SMe-tBuazaBDP nanoparticles with low power laser irradiation were proven to block cancer cell cycle, inhibit cancer cell proliferation, and induce cancer cell apoptosis in photothermal therapy (PTT). The strategy of "direct attachment of −t Bu groups to aza-BODIPY core" gives a new design platform for a photothermal therapy agent. Graphical abstract: Image 1 Highlights: Di- tert- butyl-substituted aza-BODIPYs at 3, 5-sites (tBuazaBDP s) were prepared for the first time. Near-infrared dye SMe-tBuazaBDP has the ultra-large Stokes shift (152 ​nm) in aza-BODIPY system. SMe-tBuazaBDP  ​nanoparticles can photothermally induce apoptosis as a potential photothermal therapy agent.